PROCESS INDICATORS IN CLINICAL OUTCOME OF STROKE - Ali, Amjad; Faheem, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the value of process indicators in outcome assessment of stroke patients. Material and Methods: This study was conducted at the Department of Medicine, Lady Reading Hospital, Peshawar from June 2002 to Nov 2002. Sixty patients with acute stroke were included in this study. Detailed history and full clinical examination was carried out. Data were recorded on standard proforma regarding the frequency of pressure sores, multidisciplinary involvement, distribution of Barthel Index of Activities of Daily Living (ADL) and formal swallowing assessment. These indicators were measured during admission and at six weeks follow up. Results: Neurologist and physiotherapist examine all the patients. Speech and Language Therapist (SALT) saw 50% of cases while 12 (20%) were examined each by a neurosurgeon and a psychologist. Four (6.66%) patients developed pressure sores. Formal swallowing assessment identified 17 patients to have dysphagia and those treated by SALT showed low rate of aspiration pneumonia. Distribution of Barthel score showed very low score for those patients whose both sides were involved. Patients with right sided weakness were more dependent with an average score of 14.2 (moderately dependent) as compared to patients with left-sided weakness as they had an average score of 17 (mild dependency) at six weeks. Conclusion: With routine measurement of indicators can prevent complications like pressure sores and aspiration pneumonia. This can help in selection of patients who will benefit from secondary stroke services and rehabilitation.